O léxico da apicultura e da melinponicultura no Brasil: limites e flexibilidade para sua fixação em um dicionário terminológico - Peruchi, Rosane Malusá Gonçalves [UNESP] (2014)
The relationship between man and bees dates from ancient times. In Brazil, it initially consisted of predatory extraction of honey from stingless bees and later of the introduction of bees of the genus Apis. Scientific interest concerning bees began with a search for ways to safely manage these bees and increase honey production. Currently, bee research has focused on examining the impact of these pollinating insects from socio-economic and environmental perspectives. Knowledge concerning the biology, conservation and rearing of the various species of bees directly affects environmental resilience and food security. Scientific knowledge is the key, and its dissemination is the door to access to knowledge and to the mobilization of society to protect biodiversity and prioritize sustainable agricultural production. This thesis, concerning specialized lexicography, seeks to contribute to knowledge about bees, through organization and dissemination of the terminology of this specific domain of human knowledge. It is a theoretical-methodological reflection directed towards the elaboration of a terminological dictionary. Divided into five parts, the thesis discusses the metalanguage necessary for lexicographic studies and comprehension of words as units of significance, learning and transmission of knowledge. The results include the corpus APIMELI - digital text base constituted based on Corpus linguistic principals; the facilities and limits of computational tools used for automatic extraction of vocabulary terms; the macrostructure of a dictionary with 2404 entries recorded in alphabetical order; and a pilot grouping with 225 entries of units that initiate with the letter M as an infrastructure model. This thesis conceives a terminological dictionary as a lexicographic product of semasiological orientation, to bring together a lexical collection, resulting from the linguistic interchange of specialist speakers, and a model for description ...